Electrode Fabrication and Electrochemical Analysis of AC/Graphene-Based Electrochemical Capacitor in 1 M H2SO4 - Mohd Abid, Mohd Asyadi Azam; Abdul Manaf, Nor Syafira; RAJA ABDULLAH, RAJA IZAMSHAH; Mohamad, Noraiham (American Scientific Publishers, 2014)
With the development of alternative energy research, the technology of energy storage devices has become crucial. The world is focusing on the advancement of electrochemical capacitors (ECs) or supercapacitors as one of the best energy storage devices. This paper presents the fabrication of ECs using a combination of activated carbon (AC) and graphene as active material and 1M sulfuric acid (H2SO4) as electrolyte. This work also includes analyses of electrochemical characterization such as cyclic voltammetry to obtain the specific capacitance of a device and the charge-discharge of fabricated EC. The results showed that this EC reached a specific gravimetric capacitance of up to 115.5 mF g-1 and a high rate capability, with a scan rate of up to 1,000 mV s-1. The excellent performance can be attributed to the fabrication technique, electrode material physical structures, and the intrinsic conductivity because of the AC/graphene electrode.